Usulan Perbaikan Kualitas Proses Produksi Closing Rib Perusahaan Penerbangan Dengan Metode Six Sigma - Nizar Anas; Farizi Rachman; Renanda Nia Rachmadita (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
The aim of this research evaluate the Closing Rib production process in aerospace company, trough identify the cause of product defect and find feasible solution to reduce defectedproduct. Closing Rib is a constituent component of Airbus A320 aircraft wing. Based on 2019 production data, still an average percentage of defects more than the average defect determined by the company at 1%. This study uses the Six Sigma method with concept of DMAIC (Define, Measure, Analyze, Improve, Control) in an effort to improve quality. The results of the analysis at define stage show Hole Oversized is the highest type of defect. At the measure stage, the production process stability is measured with an average proportion of defective products of 0.0818 and has one data out of control. In measuring process, the capability value is 3,6356 sigma. At analyzing the causes carried out with the FTA approach obtained 6 basic events including uniform matrix tools, poor tool storage, lack of tool identification tools, reamer usage over time, inappropriate maintenance of reamer and machine operation sequence. And in the improve stage, there are some improvement efforts such as; simplifying matrix tools, designing tool storage, creating maintenance tables for tools, and adding SOPs.